Motywacja do nauki i jej kształtowanie w świetle zrealizowanych badań - Myjak, Teresa (Kultura-Społeczeństwo-Edukacja, 2023)
The aim of the publication is to checking whether women and men, pupils and students, differ in their understanding of motivation to learn and the reasons for shaping it. The research problem was formulated in the form of questions: how is “motivation to learn” understood? and what factors shape this motivation? Two research methods were used: literature analysis and one-dimensional analysis, which was used to describe data. The presentation of the results is a quantitative summary of the answers obtained. As a research tool, an original questionnaire questionnaire was used. The considerations were focused on two issues: understanding the concept of “motivation to learn” and factors shaping motivation to learn. An intersex and intergroup analysis of the obtained research results was carried out. The results of the research procedure made it possible to isolate factors showing that motivation to learn is understood by the respondents mainly as: (1) willingness to learn depending on the ability of this action to satisfy a specific need, and: (2) a positive way of perceiving oneself as a person developing and independent in action. In shaping the motivation to learn, it is important to: (1) be interested in learning and engage in the implementation of the set goals, and: (2) the belief that thanks to science you can achieve various benefits. Empirical research has led to the general conclusion that it would be better to focus on building motivation to learn, as this can be a key factor in achieving the expected results. Activities undertaken in this direction should be comprehensive, adapted to specific conditions.